Ideal Evaluation in Islamic Education Learning - Siti Kholidatur Rodiyah (EDUTEC : Journal of Education And Technology, 2019)
A prospective teacher will actually be demanded by professionals in carrying out their duties as an educator. In teaching later a teacher is required to be able to provide the best education so as to achieve the desired educational goals. Evaluation in Islamic education the way or technique of assessment of student behavior based on a comprehensive standard calculation of all aspects of mental psychological and spiritual life of students. Because the personal figure desired by Islamic education is not only a person who is religious in nature, but also has the knowledge and skills that are capable of doing charity and worshiping God and society. In that case, educational evaluation is one part of the activities carried out by a teacher to support the achievement of educational goals, and among evaluations conducted by the teacher is the evaluation of learning outcomes, where the evaluation is carried out to measure the extent of students' knowledge and skills after receive material and direction from a teacher.Evaluation of learning outcomes is very important where a teacher must be truly objective and professional in implementing it, because on the side of a teacher will decide the success or failure of a student.